Study to development of the passive direct ethanol fuel cell by mathematical model - Saisirirat, Penyarat; Kongdai, Papopchote (Food Agricultural Sciences and Technology, 2019)
Ethanol is the interested fuel because it is low toxic and has higher energy density and it can produce from biomass. Direct ethanol fuel cell (DEFC) is the alternative fuel cell that is the sustainable energy for the portable electronic device. Now it is not easy to control the level of energy because the oxidation and reduction reactions are very slow and the crossover of water and ethanol. So this research studies the performance of the direct ethanol fuel cell especially on the passive type DEFC and interests to study three mixtures of ethanol consist of ethanol mixed with tap water, ethanol mixed with drinking water and ethanol mixed with pure distilled water. Also study about the effect of fuel cell working temperature. From which the researcher conducted the experiment to analyze the optimization of the performance of the passive direct ethanol fuel cell for the portable electronic device. This research will predict a trend of electrical potential (DEFC cell voltage) when it is out of the condition of the experiment. By using a knowledge of engineering to make a mathematical model and fi nd out the suitable condition and compare with the results of experiment and predict a trend of electrical properly.